Sustainability accounting education – a student’s perspective - Abdel K. Halabi; Alan Labas; Craig Hurley (Zeszyty Teoretyczne Rachunkowości)
Purpose: The objective of this paper is to examine whether accounting students foster changing attitudes and broader critical thinking when a new and transformative subject comprising sustainability, the environment, and the United Nations Sustainable Development Goals (SDGs) is included as part of their master's course. Methodology/approach: To determine these perceived transformative outcomes, this study relies on qualitative data derived through the written reflections of students. Reflective journals provide the voice of students, and the rich data were analysed the-matically through the NVIVO software. Findings: The reflections show that new and transformative student outcomes emerge that can stimulate meaningful action. These outcomes included changing attitudes, self-efficacy to bring about positive change, developing critical thinking, and a greater understanding of how business practices can impact the environment. Most students also noted that they would prefer to work for a business that does not harm the environment. Originality/value: There has been limited research on the attitudes of accounting students when contemporary issues such as sustainability, the environment, and the SDGs are presented in an accounting degree. The findings have added student opinions to the previous research that calls for developing a definition of accounting beyond its technical practice.